2018
DOI: 10.1158/1535-7163.mct-17-0407
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling Reveals the Glutathione Biosynthetic Pathway as a Therapeutic Target in Triple-Negative Breast Cancer

Abstract: Cancer cells can exhibit altered dependency on specific metabolic pathways and targeting these dependencies is a promising therapeutic strategy. Triple-negative breast cancer (TNBC) is an aggressive and genomically heterogeneous subset of breast cancer that is resistant to existing targeted therapies. To identify metabolic pathway dependencies in TNBC, we first conducted mass spectrometry-based metabolomics of TNBC and control cells. Relative levels of intracellular metabolites distinguished TNBC from nontrans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 43 publications
(52 reference statements)
4
43
0
Order By: Relevance
“…Survival of triple-negative breast cancer cells is dependent on the glutathione biosynthetic pathway to reduce ROS levels 21 . The source of ROS, however, has been unclear.…”
Section: Glutathione Depletion Triggers Ferroptosis In Tnbc Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival of triple-negative breast cancer cells is dependent on the glutathione biosynthetic pathway to reduce ROS levels 21 . The source of ROS, however, has been unclear.…”
Section: Glutathione Depletion Triggers Ferroptosis In Tnbc Cell Linesmentioning
confidence: 99%
“…Notably, GPX4 transcripts were not differentially expressed between these two sets of cell lines (Supplementary Figure S1c), suggesting that ferroptotic vulnerability was independent of the level GPX4 expression. We used ANOVA of our prior metabolomic data for these same cell lines to compare levels of individual metabolites 21 between TNBC cell lines susceptible to BSO-mediated ferroptosis and those that are not (as defined in Fig. 1f), and found that two of the three most significantly differentially expressed metabolites were linoleate (18:2)-substituted phosphatidylcholines, differing only in the identity of their other acyl chain ( Fig.…”
Section: Sensitivity To Ferroptosis Is Associated With the Accumulatimentioning
confidence: 99%
“…The latter study suggests that heterogeneous metabolic dependencies across cancer cell lines underly differential therapeutic vulnerabilities associated with specific cancer genotypes 22 . Direct targeting of metabolic states in TNBC has shown promising results, for example, inhibitors that target glutathione biosynthesis, folate receptor, fatty acid oxidation as well as glutamine metabolism were shown to suppress tumor growth in TNBC 26,27,50,51 . However, successful clinical translation of these results is hampered by issues such as metabolic plasticity 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of γ-glutamylcysteine ligase, the rate-limiting enzyme in glutathione biosynthesis, had significantly poorer survival. 28 Hypoxia causes ROS imbalance, which may be associated with drug resistance and metastasis. Antioxidant system is balanced by nuclear factor erythroid-2-related factor 2 (NFE2L2, Nrf2) and…”
Section: Cancer and Metabolomic Profilingmentioning
confidence: 99%
“…TNBC shows lower levels of glutathione compared with normal cells, thus sensitive to inhibitors of glutathione biosynthesis that was rescued by N‐acetylcysteine, demonstrating a dependence on glutathione production to suppress ROS and support tumor cell survival. Moreover, high levels of γ‐glutamylcysteine ligase, the rate‐limiting enzyme in glutathione biosynthesis, had significantly poorer survival …”
Section: Introductionmentioning
confidence: 99%